Inventory Of Land Destruction Arrangements - amienatul rasyida (Law Research Review Quarterly, 2024)
Perished land is land that has changed its original form due to natural events, so that it can no longer be utilized, functioned and identified. A land right can be extinguished if the land falls to the state, because it is voluntary, because it is abandoned, and the land is destroyed. Several plots of land in Sriwulan Village, Bedono Village, and Purwosari Village, Sayung Subdistrict were declared destroyed due to natural events, so that they were utilized as a form of land acquisition for the public interest in the construction of the Semarang-Demak Toll Road. This research uses empirical juridical methods with a qualitative approach based on field research by examining statutory provisions and interviews in the field in order to obtain the facts. The results obtained from this research are (1) The regulation of the destroyed land is regulated in Permen ATR / BPN No. 3 of 2024 on the amendment of Permen No. 17 of 2021 concerning Procedures for Determining Destruction Land, and Presidential Regulation No. 27 of 2023 on the amendment of Presidential Regulation No. 52 of 2022 concerning Handling Social Impacts on Land Identified as Destruction Land in the context of Development for the public interest. (2) The legal protection provided by the state is compensation in the form of a Compensation Fund.